1973
DOI: 10.1099/00221287-74-1-93
|View full text |Cite
|
Sign up to set email alerts
|

Translation of RNA Coliphages by Amino Acid-incorporation Systems of the Enterobacteriaceae

Abstract: S U M M A R YCrude cell-free amino acid-incorporating systems derived from a variety of enterobacterial species are not uniform in their ability to translate RNA of the coliphages Qp or MS 2 . Escherichia coli, Shigella alkalescens and to a lesser extent Citrobacter freundii translate effectively under standard conditions, but Salmonella typhimurium, S. pomona and Proteus morganii do not. Ineffective species do not generally inactivate phage RNA faster than effective ones, and they are as effective as E. coli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1973
1973
1979
1979

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Himes et al (4) have reported that Clostridium pasteurianum extracts fail to translate f2 RNA, and Stallcup and Rabinowitz (16,17) have further characterized the clostridial system. Howk et al (5) have reported that extracts of some species of Enterobacteriaceae, including S. typhimurium, are unable to translate MS2 or Q,B RNA.…”
mentioning
confidence: 99%
“…Himes et al (4) have reported that Clostridium pasteurianum extracts fail to translate f2 RNA, and Stallcup and Rabinowitz (16,17) have further characterized the clostridial system. Howk et al (5) have reported that extracts of some species of Enterobacteriaceae, including S. typhimurium, are unable to translate MS2 or Q,B RNA.…”
mentioning
confidence: 99%